Silat: Malay heritage heroism; case study on the perception among university student in UiTM Malacca city campus / Muhammad Shamsul Suhaimi - Suhaimi, Muhammad Shamsul (2014)
The intention of this research are be doing is to introduce silat in general.The part of this research an overview of silat and its history.The history and founder are detailed.A glimpse of silat hierarchy is presented so that readers will understand the evolution or rather revolution that took place from the early period until present. A section about the connotion ofsilat,it's philosophy and the adat (culture and tradition) is also included.There is a commonly asked questions and answers section.Because silat is an art predominantly practiced by people in Southeast Asia,at the end of the research,classical names of silat styles are included as a references.The famous story of two Malay Warrior,Hang Tuah and Hang Jebat,is also included to give insight into how silat and adat are related to the story.Because silat is native Malaysia,a tour of the country is provided.